1991. A Prospective Pilot Evaluation of a Research Use Only (RUO) Prototype of a Highly Multiplexed Sample-to-Answer PCR System for the Detection of Pathogens From Positive Blood Culture. (26th November 2018) - Spaulding, Usha; Stone, Jessica; Koch, Kerrin; Antosch, Jeremiah; Jones, Matthew; Lu, Zhenmei; Todorov, Toma; Kerr, Scott; Holmberg, Kristen; Rogatcheva, Margarita
Abstract: Background: Rapid identification of causative agents from positive blood culture (PBC) can aid earlier targeted therapy, as well as reduce mortality, length of stay, and costs associated with systemic infections. The BioFire® Blood Culture Identification 2 (BCID2) Panel being developed by BioFire Diagnostics, LLC, aims to maintain or improve the performance of the BioFire® FilmArray® Blood Culture Identification (BCID) Panel with updated and novel assays (15 new analytes: six antimicrobial resistance (AMR), six bacterial, and three fungal analytes). The performance of an RUO BioFire BCID2 Panel during a prospective pilot study is compared with standard of care (SoC), as well as independent PCR comparator assay (compPCR) results. Methods: Two pilot sites enrolled de-identified PBC (<24 hours post-positivity) for which clinician-ordered SoC tests had been performed. Aliquots of residual PBC and isolates were frozen for compPCR testing of AMR markers and discrepancy resolution. 100 aerobic PBC (A-PBC) and 85 anaerobic PBC (AN-PBC) were tested with the BioFire BCID2 Panel; 70 A-PBCs and 56 AN-PBCs were concurrently tested on BioFire BCID Panel. Also, isolates from PBCs positive for AMR markers were tested using compPCR. Results: The BioFire BCID2 Panel results matched SoC results in 176/177 detections from 100 A-PBC, and in 167/168 detections from 85 AN-PBC. Both BioFire panels detected Candida glabrata and Candida parapsilosis from an A-PBC with only C. parapsilosis SOC result; interestingly, C. glabrata was detected by SoC in the paired AN-PBC. False-positive Bacteroides fragilis detection in an AN-PBC was resolved favorably by compPCR. Two patient samples, positive in both A-PBC and AN-PBC by SoC, were not detected by either the Staphylococcus epidermidis or the Staphylococcus spp. assays on the BioFire BCID2 Panel. All 26 AMR marker detections in both types of PBC were concordant with either SoC or compPCR results. Conclusion: With an expanded menu, >99% specificity, and >97% sensitivity, the BioFire BCID2 Panel is expected to provide rapid and accurate results for key pathogens associated with systemic infections, as well as important AMR markers. RUO products used in this study have not been evaluated by the FDA or other regulatory agencies for In Vitro Diagnostic use. Disclosures: U. Spaulding, BioFire Diagnostics, LLC: Employee, Salary. J. Stone, BioFire Diagnostics, LLC: Employee, Salary. K. Koch, BioFire Diagnostics, LLC: Employee, Salary. J. Antosch, BioFire Diagnostics, LLC: Employee, Salary. M. Jones, BioFire Diagnostics, LLC: Employee, Salary. Z. Lu, BioFire Diagnostics, LLC: Employee, Salary. T. Todorov, BioFire Diagnostics, LLC: Employee, Salary. S. Kerr, BioFire Diagnostics, LLC: Employee, Salary. K. Holmberg, BioFire Diagnostics, LLC: Employee, Salary. M. Rogatcheva, BioFire: Employee, Salary.